The wavefield of acoustic logging in a cased-hole with a single casing – Part I: a monopole tool. Issue 1 (12th October 2017) - Wang, Hua; Fehler, Michael
SUMMARY: The bonding quality of the seal formed by the cement or collapse material between casing and formation rock is critical for the hydraulic isolation of reservoir layers with shallow aquifers, production and environmental safety, and plug and abandonment issues. Acoustic logging is a very good tool for evaluating the condition of the bond between different interfaces. The understanding of the acoustic logging wavefields in wells with single casing is still incomplete. We use a 3-D finite difference method to simulate wireline monopole wavefields in a single cased borehole with different bonding conditions at two locations: (1) between the cement and casing and (2) between the cement and formation. Pressure snapshots and waveforms for different models are shown, which allow us to better understand the wave propagation. Modal dispersion curves and data processing methods such as velocity–time semblance and dispersion analysis facilitate the identification of propagation modes in the different models. We find that the P wave is submerged in the casing modes and the S wave has poor coherency when the cement is replaced with fluid. The casing modes are strong when cement next to the casing is partially or fully replaced with fluid. The amplitude of these casing modes can be used to determine the bonding condition of the interface between casing and cement. However, the limited variation of the amplitude with fluid thickness means that amplitude measurements may lead to an ambiguous interpretation. When the cement next to the formation is partially replaced with fluid, the modes propagate in the combination of steel casing and cement and the velocities are highly dependent on the cement thickness. However, if the cement thickness is large (more than 2/3 of the annulus between casing and rock), the arrival time of the first arrival approximates that of the formation compressional wave when cement is good. It would highly likely that an analyst could misjudge cement quality because the amplitudes of these modes are very small and their arrival times are very near to the formation P arrival time. It is possible to use the amplitude to estimate the thickness of the cement sheath because the variation of amplitude with thickness is strong. While the Stoneley mode (ST1) propagates in the borehole fluid, a slow Stoneley mode (ST2) appears when there is a fluid column in the annulus between the casing and formation rock. The velocity of ST2 is sensitive to the total thickness of the fluid column in the annulus independent of the location of the fluid in the casing annulus. We propose a full waveform method, which includes the utilization of the amplitude of the first arrival and also the velocity of the ST2 wave, to estimate the bonding condition of multiple interfaces. These two measurements provide more information than the current method that uses only the first arrival to evaluate the bonding interfa next to the casing.